Electrochemical behavior of ionic and metallic zirconium in ionic liquids - Ashraf, Muhammad Adeel; Valtiner, Markus; Gavrilovic-Wohlmuther, Aleksandra; Kampichler, Juliane; Pichler, Christian M. (Frontiers in Chemical Engineering, 2022)
Metallic zirconium has a broad range of potential applications in engineering and in industries that are operating under harsh corrosive environments, such as nuclear and chemical industry. Compared to other metals like aluminum, its behavior in electrochemical reactions is poorly understood and so far there are no larger-scale electrochemical approaches to process zirconium. Ionic liquids are a suitable reaction medium for electrochemical reactions of zirconium. To better understand the electrochemical reactivity of zirconium, different combinations of ionic liquids and zirconium precursors are investigated. It was found that interactions between the Zr precursor and the ionic liquids can have significant influence on the diffusion properties of Zr. Furthermore, mixtures of ionic liquids with other solvents were explored and it could be determined that most of the electrochemical properties of Zr are retained also in solvent mixtures. This could potentially save costs for industrial applications, as lower amounts of the ionic liquids can be used, to obtain similar electrochemical properties.